(untitled) (Journal of Educational Sciences, 2016)
This paper presents research findings of a case-study of students’ participation in the Erasmus Mundus Program at L.N. Gumilyov Eurasian National University. Data analysis is based on the results of survey among ENU students who have already participated in the Program and those who are not. The main results of the study may have implications for further research in the field of internationalization and development of both inbound and outbound mobility. The study was conducted within the project “Internationalization as a strategic factor in the development of education and science of the Republic of Kazakhstan in social-economic globalization”. It is established that in the period from 2007 to 2013, Kazakhstan became a party to 22 projects Erasmus Mundus. The total number of Kazakhstani universities involved or participating in Erasmus Mundus accounted for 23 of the University. L.N. Gumilyov Eurasian national University is a participant of the 11 projects; al-Farabi KazNU, T. Ryskulov KazEU participated in 7 projects of the program. In conjunction with K. Satpayev national technical University respectively 6 and 5 projects. Other universities participated in the program of 4 and less time.